Examining Bulgaria's current lack of performance at elite sport level - Tsonev, Martin (2017)
In the past few decades, professional sport in Bulgaria has been experiencing difficulties in performing well at an elite level. The country fails to live up to the standard that was established prior to the political changes in 1989. However, little to no research has been done, in order to examine the reasons behind this lack of performance by Bulgarian athletes and teams. Therefore, the goal of this study is to focus on the issues that might hinder the development of professional athletes and their performance. The research uses De Bosscher’s SPLISS model which is a conceptual framework whose goal is to analyze sport policy factors leading to international success. For the purpose of this study, a qualitative phenomenological research method was applied. 8 semi-structured interviews were conductedwith people in Bulgaria who are directly involved in the development of sport in the country and are aware of the ongoing problems that teams and athletes face. Those people include physical education teachers (3), youth academy coaches (3) and youth academy players (2). As part of the research, they were asked various questions in relation to the SPLISS model’s content. Following the structure of the SPLISS model it became evident that Bulgarian sport is falling behind in its development which is caused by a lack of sufficient funding, sport policies and regulation which do not facilitate the progress of young talent and teams in the country. There are also numerous factors in play in terms of sport as a priority among people. According to the participants, there is also a certain level of distrust in the current system, caused by the inept efforts of the state to support athletes during and after their careers. The absence of an established talent identification system is also a problem that needs to be addressed in order for Bulgarian sport to overcome its struggles. Recommendations for further research are also pointed out at the end of this master thesis. That includes a quantitative approach instead of qualitative one, which would reach a larger field of participants delivering more detailed data.